Reasoning, cognitive control, and moral intuition - Patterson, Richard; Rothstein, Jared; Barbey, Aron K. (Frontiers in Integrative Neuroscience, 2012)
Recent “Social Intuitionist” work suggests that moral judgments are intuitive (not based on conscious deliberation or any significant chain of inference), and that the reasons we produce to explain or justify our judgments and actions are for the most part post hoc rationalizations rather than the actual source of those judgments. This is consistent with work on judgment and explanation in other domains, and it correctly challenges one-sidedly “rationalistic” accounts. We suggest that in fact reasoning has a great deal of influence on moral judgments and on intuitive judgments in general. This influence is not apparent from study of judgments simply in their immediate context, but it is crucial for the question of how cognition can help us avoid deleterious effects and enhance potentially beneficial effects of affect on judgment, action, and cognition itself. We begin with established work on several reactive strategies for cognitive control of affect (e.g., suppression, reappraisal), then give special attention to more complex sorts of conflict (“extended deliberation”) involving multiple interacting factors, both affective and reflective. These situations are especially difficult to study in a controlled way, but we propose some possible experimental approaches. We then review proactive strategies for control, including “avoidance of temptation” and mindfulness meditation (Froeliger, et al, 2012, This Issue). We give special attention to the role of slow or “cool” cognitive processes (e.g., deliberation, planning, executive control) in the inculcation of long-term dispositions, traits, intuitions, skills or habits. The latter are critical because they in turn give rise to a great many of our fast, intuitive judgments. The reasoning processes involved here are distinct from post hoc rationalizations and have a very real impact on countless intuitive judgments in concrete situations. This calls for a substantial enlargement of research on cognitive control.